PERAN MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PROFESIONALISME GURU DI SMAN 1 PARINGIN - Miranti Miranti (ADISAM PUBLISHER, 2023)
The principal is a leader, mover, motivator, planner, evaluator, and various other names that have deep meaning as a manager. With the words of this leader, the entire school line is under his responsibility. The principal also holds responsibility for the management of all elements within the institution. The elements of this institution include teaching staff, educational staff and all students who will obey and obey the school principal. The principal himself has several functions. But the main function of the principal is managerial. The managerial functions of school principals include planning, implementing, and evaluating or better known as POAC (Planning, Organizing, Actuating, Controlling). This managerial function also supports all elements within the institution, one of which is for educators. Educators are the parties who directly carry out the educational process, so the managerial role of the school principal in increasing the professionalism of teaching staff is very much needed in an institution. This study aims to find out 1) How school principals develop a program to improve the quality of teacher professionalism at SMAN 1 Paringin, 2) How school principals implement a program to improve the quality of teacher professionalism at SMAN 1 Paringin, 3) How school principals evaluate programs to improve the quality of teacher professionalism at SMAN 1 Paringin. The method used by the author in this research is qualitative research, in which data is obtained from people and behavior that can be observed through interviews, observation and documentation. Who seek to research or conduct observational studies. From the results of research at SMAN 1 Paringin it can be concluded as follows: 1) The school principal prepares a strategic plan in which short term, medium term and long term programs. The preparation was carried out together with a team consisting of 6 components, namely the principal, teacher, Ka. TU, committee, representatives of student guardians and educational resource persons. 2) The implementation of the program went well even though there were obstacles and factors that bound the program participants, so that the program could run according to the plan with a percentage of 60-85%. 3) The school principal always controls the entire series of programs and evaluates various programs, such as long- term programs, is reviewed at every meeting and revised as needed